Low-level overexpression of wild type TDP-43 causes late-onset, progressive neurodegeneration and paralysis in mice. - Chunxing Yang; Tao Qiao; Jia Yu; Hongyan Wang; Yansu Guo; Johnny Salameh; Jake Metterville; Sepideh Parsi; Issa Yusuf; Robert H Brown; Huaibin Cai; Zuoshang Xu (PLoS ONE)
Modestly increased expression of transactive response DNA binding protein (TDP-43) gene have been reported in amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), and other neuromuscular diseases. However, whether this modest elevation triggers neurodegeneration is not known. Although high levels of TDP-43 overexpression have been modeled in mice and shown to cause early death, models with low-level overexpression that mimic the human condition have not been established. In this study, transgenic mice overexpressing wild type TDP-43 at less than 60% above the endogenous CNS levels were constructed, and their phenotypes analyzed by a variety of techniques, including biochemical, molecular, histological, behavioral techniques and electromyography. The TDP-43 transgene was expressed in neurons, astrocytes, and oligodendrocytes in the cortex and predominantly in astrocytes and oligodendrocytes in the spinal cord. The mice developed a reproducible progressive weakness ending in paralysis in mid-life. Detailed analysis showed ~30% loss of large pyramidal neurons in the layer V motor cortex; in the spinal cord, severe demyelination was accompanied by oligodendrocyte injury, protein aggregation, astrogliosis and microgliosis, and elevation of neuroinflammation. Surprisingly, there was no loss of lower motor neurons in the lumbar spinal cord despite the complete paralysis of the hindlimbs. However, denervation was detected at the neuromuscular junction. These results demonstrate that low-level TDP-43 overexpression can cause diverse aspects of ALS, including late-onset and progressive motor dysfunction, neuroinflammation, and neurodegeneration. Our findings suggest that persistent modest elevations in TDP-43 expression can lead to ALS and other neurological disorders involving TDP-43 proteinopathy. Because of the predictable and progressive clinical paralytic phenotype, this transgenic mouse model will be useful in preclinical trial of therapeutics targeting neurological disorders associated with elevated levels of TDP-43.